2016
DOI: 10.1136/heartjnl-2016-309673
|View full text |Cite
|
Sign up to set email alerts
|

Galectin-3 predicts left ventricular remodelling after anterior-wall myocardial infarction treated by primary percutaneous coronary intervention

Abstract: Gal-3 serum levels measured during hospitalisation could be clinically useful in predicting LVR among patients admitted with anterior STEMI treated by pPCI.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
25
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(26 citation statements)
references
References 30 publications
(30 reference statements)
1
25
0
Order By: Relevance
“…Prospective 103 STEMI patients treated by pPCI Elevated Gal-3 levels at baseline are an independent predictor of LVR at 6 month follow-up [49] George et al No association between Gal-3 and heart failure [4] MI, myocardial infarction; STEMI, ST-Segment Elevation Myocardial Infarction; N-STEMI, non-ST segment elevation myocardial infarction; CAD, coronary artery disease; LVEF, left ventricular ejection fraction; MACO, major adverse clinical outcome; pPCI, primary percutaneous coronary intervention; LVR, left ventricular remodeling; ACS, acute coronary syndrome; CSA, chronic stable angina; MVA, microvascular angina; HF, heart failure; UA, unstable angina; AF, atrial fibrillation.…”
Section: Prospective 26 Stemi Patientsmentioning
confidence: 99%
See 1 more Smart Citation
“…Prospective 103 STEMI patients treated by pPCI Elevated Gal-3 levels at baseline are an independent predictor of LVR at 6 month follow-up [49] George et al No association between Gal-3 and heart failure [4] MI, myocardial infarction; STEMI, ST-Segment Elevation Myocardial Infarction; N-STEMI, non-ST segment elevation myocardial infarction; CAD, coronary artery disease; LVEF, left ventricular ejection fraction; MACO, major adverse clinical outcome; pPCI, primary percutaneous coronary intervention; LVR, left ventricular remodeling; ACS, acute coronary syndrome; CSA, chronic stable angina; MVA, microvascular angina; HF, heart failure; UA, unstable angina; AF, atrial fibrillation.…”
Section: Prospective 26 Stemi Patientsmentioning
confidence: 99%
“…In particular, they assessed LV remodeling with extracellular volume fraction (ECV), determined by cardiovascular magnetic resonance (CMR). In a larger cohort comprising 103 STEMI patients treated by pPCI, Di Tano et al found Gal-3 is an independent predictor of LVR after MI [49]. LVR was defined as a ≥ 15% increase in LV end-systolic volume.…”
Section: Gal-3 and Prognosismentioning
confidence: 99%
“…Although plasma Gal-3 at Day 7 was related to myocardial extracellular volume fraction at six months in patients after acute myocardial infarction [49], other reports on the association of baseline Gal-3 with LV remodeling brought contradictory results [50,51,52]. As to severe AS, circulating Gal-3 did not correlate with percent collagen area or the number of macrophages in tissue samples collected from the basal interventricular septum at the time of valve surgery for AS [22].…”
Section: Discussionmentioning
confidence: 99%
“…Irrespective of LV ejection fraction and infarct size, galectin-3 measured during hospitalization predicted adverse LV remodelling defined as an increase of at least 15% of LV end-diastolic volume after 6 months in patients with anterior STEMI. 25 Furthermore in a translational porcine model of coronary microembolisminduced postischaemic cardiac remodelling, galectin-3 could be localized in areas of tissue damage and myocardial fibrosis, with proportionate increase in the respective serum galectin-3 expression levels. 26 Another translational murine model could identify galectin-3 as a mediator of postischaemic, macrophage mediated myocardial inflammation and suggested it may represent a potential target for therapeutic inhibition.…”
Section: Soluble Galectin-3 Is Associated With Premature Myocardialmentioning
confidence: 99%